Molecular and morphological diversity in species of Kronichthys (Teleostei, Loricariidae) from Atlantic coastal rivers of Brazil - Souza, Camila S. [UNESP]; Silva, Gabriel S. C. [UNESP]; Ochoa, Luz E.; Roxo, Fabio F. [UNESP]; Costa-Silva, Guilherme J.; Foresti, Fausto [UNESP]; Melo, Bruno F. [UNESP]; Oliveira, Claudio [UNESP] (Wiley-Blackwell, 2020)
The Neotropical catfish genus Kronichthys contains three species distributed along coastal rivers of southern and southeastern Brazil. Although phylogenetic hypotheses are available, the molecular and morphological diversity and species boundaries within the genus remain unexplored. In this study, the authors generated mitochondrial data for 90 specimens combined with morphometric and meristic data to investigate species diversity, species boundaries and putative morphological signatures in Kronichthys. Phylogenetic and species delimitation results clearly show the presence of four genetic lineages, three within Kronichthys heylandi along the coast from Rio de Janeiro to southern Sao Paulo and a single lineage encompassing both the nominal species Kronichthys lacerta and Kronichthys subteres from the Ribeira de Iguape basin to Santa Catarina in southern Brazil. Nonetheless, morphological data show overlapped ranges in morphometrics and a definition of only two morphotypes, with clear phenotypic differences in the teeth number: K. heylandi differs from K. subteres + K. lacerta by the higher number of premaxillary teeth (30-52 vs. 19-28) and higher number of dentary teeth (28-54 vs. 17-28). Headwater captures and connections of paleodrainages because of sea-level fluctuations represent the two major biogeographic processes promoting species diversification and lineage dispersal of Kronichthys in the Atlantic coastal range of Brazil.
Keywords: diversity; Hypoptopomatinae; Serra do Mar; species delimitation; systematics